THE USE OF DISCITE APP TOOL IN ENGLISH TEST - Ahmad Muqtadir; Erwin Akib; Yasser Mallappiang (FKIP Unismuh Makassar, 2022)
AHMAD MUQTADIR 2022. The Use of Discite App Tool in English Test (Descriptive Quantitative Research). A Thesis of English Education Department. Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervised by Erwin Akib and Yassir Malappiang. This research aimed to find out how multimedia Discite app tool is used in evaluating students’ english test and also the students’ response toward Discite app tool. The subjects of this research we the English teacher at the ninth grade and the students of the ninth grade students. It was chosen by using cluster sampling. The design of this study was descriptive quantitative. The instruments of this research were English Test, Observation and Questionnaires. The result of the data indicated that, first the value 90% is obtained as a percentage of the results of validation by the English teacher on the product. With this result, conclusions can be made about feasibility of English test developed by using Multimedia Authoring Tool. The feasibility of the product is very good or very interesting to be implemented in test. In general, the English teacher assess that the media is suitable for use. As for the advice, the test needs to add some picture because some of them are still not clear enough. Then it can make the test more interested and easy to answer. Second, The results of assessment from the students toward the product above show that the average value is 95%. In this process the students looked enthusiast in answering the test. They could know their answer was correct or incorrect after click submit button, it made them motivated more to answer the next question. Besides, some students feel uncomfortable with picture, combination colour and the instruction. By trial and testing with students in class the researcher found some parts need to be corrected in the product. The parts need to be corrected are combination colour, more instruction and need more picture to make it more interested.